Exploring effects of hotel chain loyalty program - Pimpão, Pedro (2022)
Purpose – The main purpose of this work is to evaluate the long-term effectiveness of a hotel’s chain loyalty program from a behavioral perspective. Design/methodology/approach – A Dirichlet model was estimated to assess purchase frequency and hotel choice within one of the biggest hotel chains in Portugal. The sample comprises hotels where a loyalty program was implemented, with a total of 176,099 reservations. Data were extracted from the customer relationship management (CRM) systems of the hotel group. Findings – The results suggest that instead of being loyal to a certain hotel, customers are loyal to the branded hotel chain. As the hotels are all part of the branded group, this polygamy is not only accepted but also very welcome. Research limitations/implications – The level of penetration and purchase frequency of CRM was measured. Nevertheless, a thorough understanding of these will be critical for the success of this program. Practical implications – This research is a step toward assessing hotel chain competitiveness, by improving and suggesting segmented groups of brands/hotels and to induce cross-selling products accepting polygamous loyalty as the only way to sustain long-term relationships with customers. Originality/value – This is one of the few research studies, if not the only one, to assess loyalty with tangible indicators, such as purchase frequency. Further, the results suggest that loyalty programs are more effective if multiple options are available and as such, cross-selling is perhaps the only way to fix customers.